Simulation and Analysis of Thermal Insulators Applied to Post-Disaster Temporary Shelters in Tropical Countries - Bruno B. F. da Costa; Caio F. P. Silva; Ana Carolina Fernandes Maciel; Herson D. P. Cusi; Gladys Maquera; Assed Haddad (My University, 2023)
Containers are fundamental elements for the development of international trade; however, it is estimated that there are more than 17 million retired containers stacked in ports around the world. Considering the high costs involved in the process of storing, transporting, or destroying these materials, in addition to their non-degradable nature, it is urgent to develop strategies for the sustainable use of these decommissioned containers. In this context, repurposing these containers into permanent structures is becoming a predominant trend. One solution is converting steel shipping structures into habitable spaces. However, due to the urgency with which Container Houses (CHs) are demanded in case of disasters, they are usually planned to be built as quickly as possible, serving as many people as possible, and do not consider the basic principles of energy efficiency. The performance of the CHs is, then, impaired, including risks of overheating, corrosion, and rust, among others, during service, making them an even more stressful experience for their users who are already in a vulnerable situation. Therefore, the objective of this study is to compare the performance of two thermal insulators applied to a temporary shelter container designed to promptly serve vulnerable populations. The model was developed in Building Information Modeling (BIM) software and simulated in Building Energy Simulation (BES) software, aiming to obtain subsidies for its technical and economic viability analysis. The results indicated that thermal insulators are able to generate significant savings in energy consumption, with mineral wool presenting better long-term performance.
Keywords: Context (archaeology); Container (type theory); Business; Environmental economics; Architectural engineering; Computer science; Environmental science; Engineering; Mechanical engineering; Paleontology; Biology; Economics; Context (archaeology); Container (type theory); Business; Environmental economics; Architectural engineering; Computer science; Environmental science; Engineering; Mechanical engineering; Physical Sciences Engineering Building and Construction BIM and Construction Integration; Social Sciences Psychology Social Psychology Facilities and Workplace Management; Physical Sciences Engineering Industrial and Manufacturing Engineering Advanced Manufacturing and Logistics Optimization